2016
DOI: 10.1364/ol.41.001408
|View full text |Cite
|
Sign up to set email alerts
|

Linear mode conversion of terahertz radiation into terahertz surface magnetoplasmons on a rippled surface of magnetized n-InSb

Abstract: A new mechanics of linear mode conversion of terahertz (THz) radiation into THz surface magnetoplasmons on a rippled surface of magnetized n-InSb is proposed. The normally incident THz radiation, polarized in the direction of a ripple wave vector, imparts oscillatory velocity to electrons in the ripple layer. This velocity beats with surface ripple to produce a nonlinear current that resonantly drives the THz surface magnetoplasmons. In the presence of an applied magnetic field, the surface plasmon (SP) mode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Another proof of GOD's communication with the living/non-living matter was given by Kumar et al [2]. In this paper Kumar et al has shown that any radiation falling on the rippled surface under the presence of magnetic field get converted into surface magnetoplasmons, so from this inference can be easily drawn how life is affected by universal phenomenon as every matter radiates its own energy in the form of radiation depending upon its characteristic and thus affect the life.…”
Section: Introductionmentioning
confidence: 93%
“…Another proof of GOD's communication with the living/non-living matter was given by Kumar et al [2]. In this paper Kumar et al has shown that any radiation falling on the rippled surface under the presence of magnetic field get converted into surface magnetoplasmons, so from this inference can be easily drawn how life is affected by universal phenomenon as every matter radiates its own energy in the form of radiation depending upon its characteristic and thus affect the life.…”
Section: Introductionmentioning
confidence: 93%
“…Let us assume a x = 0 is a interface of rippled n-type semiconductor ( x ≤ 0) and free space (x > 0), and n-type semiconductor rippled surface with modulated perturbed electron density n = (n 0 /2)(1+cos qz) [20], qa ≥ 1, q and a are the rippled wave number and amplitude of the rippled respectively in the existence of external magnetic B 0 ŷ (cf. Fig.…”
Section: Nonlinear Current Densitymentioning
confidence: 99%
“…Bhasin and Tripathi [19] analytically examined the THz generation by optical rectification on the rippled density of the magnetized plasma. Kumar et al [20] studied the excitation of THz SMPs over the n-InSb by linear mode conversion of THz radiation. Srivastav and Panwar [21] analytically derived generation of THz SMPs on rippled surface of n-InSb in the presence of external magnetic field by nonlinear mixing of two laser beams.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission, polarization, and magnetooptical properties of InSb have been widely investigated in recent years. [31][32][33][34][35][36][37][38][39][40][41][42] For instance, in 2018, Lin et al [36] reported a nonreciprocal THz reflection on the InSb with the transverse magneto-optical effect (i.e., Voigt configuration). This one-way mirror achieves 35 dB isolation with 6.2 dB insertion loss for a certain linearly polarized (LP) state.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission, polarization, and magneto‐optical properties of InSb have been widely investigated in recent years. [ 31–42 ] For instance, in 2018, Lin et al. [ 36 ] reported a nonreciprocal THz reflection on the InSb with the transverse magneto‐optical effect (i.e., Voigt configuration).…”
Section: Introductionmentioning
confidence: 99%